Exercise prescriptions for young people’s emotional wellbeing: a systematic review of physical activity intensity, duration, and modality - Huang, Wanyu; Wong, Tong Lam (Frontiers in Psychology, 2025)
ObjectivePhysical activity (PA) is beneficial to the body and effective in promoting mental health and social relationships, which is one of the most important ways to enhance the quality of life. This review investigated the effects of PA in intensity, duration, and exercise modality on young people’s mood.MethodsAdhering to PRISMA 2020 guidelines, this study conducted a meticulous search across the Web of Science, PubMed, PsycINFO, and Scopus from May to July 2024, and participants aged between 13 and 28 were specified for inclusion in the study. The search yielded 942 titles and abstracts, and subsequent screening according to the criteria led to the inclusion of 20 studies, with 11 focusing on exercise intensity, four on duration, and five on exercise modality.ResultsExercise of different intensities and durations had different effects on mood, with moderate intensity having the most significant effect on mood. In terms of duration, exercise lasting 10–30 min was more effective in improving positive mood. In addition, the effects of different modalities of exercise on mood also vary, with current research focusing more on the effects of aerobic exercise on mood.ConclusionPA can have a positive impact on mental health that varies by intensity, duration, and modality of exercise; moderate intensity and 30 min of exercise tend to result in the most positive emotions. More research could be conducted in the future in different anaerobic exercises.